Genetic characterization of clones and varieties of Cenchrus purpureus with microsatellite markers - González, C.; Martínez, R. O. (Cuban Journal of Agricultural Science, 2019)
This study determined the genetic diversity in 15 varieties and clones of Cenchrus purpureus with 11 SSR microsatellite DNA markers identified in pearl millet (Cenchrus americanus). Results indicated polymorphism in the SSR markers, which amplified 68 fragments in total, of which 57 were polymorphic and 7 appeared in a single genotype. Markers CTM8 (DI = 0.88), PSMP2255 (DI = 0.71), PSMP2267 (DI = 0.74) and PGIRD56 (DI = 0.74) showed the highest diversity indixes. Dice distance coefficients ranged from 0.04 to 0.63, indicating high genetic variability among the accessions. Genotypes were divided into three groups in which King grass and OM-22 varieties were not included. The three groups were composed by the genotypes suitable for grazing. The use of these markers is suggested to evaluate genetic diversity in the 56 accessions conserved in the Instituto de Ciencia Animal germplasm bank. Keywords: livestock, forage, genetic improvement